Pengaruh edukasi gizi dengan media puzzle terhadap pengetahuan tumpeng gizi seimbang pada anak sekolah - Siti Maqhfirah; Arnisam Arnisam (Nutrition and Health Insights, 2025)
Nutritional issues in society are one of the crucial factors that play a role in determining the success of human development in Indonesia. The main factors that directly affect nutritional problems include the imbalance between food intake and body needs, unbalanced nutrition, and the presence of infectious. The purpose of this study was to determine the effect of nutrition education with puzzle media on knowledge about a balanced nutritional cone in school children in uptd sd negeri 3 gandapura. The design in this study is quasi experimental, which was conducted at UPTD SD Negeri 3 Gandapura starting from April 16 to April 20, 2024. The data collection is primary data, in the form of knowledge of school-age children menganai balanced nutrition tumpeng obtained through pretest and post-test. Data processing in this study includes knowledge data, giving a score or raw value to each answer with a value of 1 for the correct answer and 0 for the wrong answer, then analyzed and tested non-parametric statistics, namely the Wilcoxon test. The average knowledge of students before being given counseling with puzzle media is 63.04 with a deviation of 10.897, and after being given puzzle media it increases to an average of 83.21 with a deviation of 9.519. The statistical test used, namely the Wilcoxon Test, obtained a significant value of 0.000, which means that there is an effect of nutrition education with puzzle media on knowledge about balanced nutrition in UPTD SD Negeri 3 Gandapura. There is an effect of nutrition education with puzzle media on knowledge about a balanced nutritional cone in school-age children (P <0.05).